The Effect of Stock Trading Volume, Abnormal Return, and Bid-Ask Spread Before and After Stock Split Events on Companies on the Indonesia Stock Exchange - Noor Maulia Minzani; Abdul Rakhman Laba; Fauzi Rahman Rahim (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
This study aims to determine the difference between Stock Trading Volume, Abnormal Return, and Bid-Ask Spread Before and After Stock Split Events in Companies on the IDX. Data collection uses secondary data obtained through stock price movement data using purposive sampling technique. The population is all companies listed on the IDX that conducted a Stock Split for the 2018-2020 period of 23 companies, while the sample taken was 18 companies. Test the hypothesis using the Two-Mean Difference Test with the Paired Sample T-Test technique with an observation period of 5 weeks before and after the stock split. The results showed that the hypothesis proposed that the stock trading volume before and after the stock split found no significant difference.